From Multiplicative Growth to Institutionalized Exponential Knowledge: A Praxeological Analysis of Exponential Learning in a Secondary Mathematics Textbook - Laila Cantika; Septiani Yugni Maudy; Mulia Putra (Jurnal Didactical Mathematics, 2026)
This study investigates the praxeological organization of exponent learning in a Grade 10 mathematics textbook through the lens of the Anthropological Theory of the Didactic (ATD). The study aims to examine how exponent knowledge is introduced, developed, and institutionalized through the relationships among tasks, techniques, technologies, and theories. A qualitative document analysis was conducted using the exponent chapter of the 2021 Indonesian Mathematics Electronic School Book. The analysis focused on Exploration 1.1, Exploration 1.2, and Exercise 1.1, which cover the initial development of concepts of exponents. Mathematical tasks were identified and reconstructed into local praxeologies, which were subsequently synthesized into a global praxeological organization. The findings reveal a coherent learning trajectory consisting of three successive phases. Exploration 1.1 constructs exponentiation through multiplicative growth situations, enabling students to develop meaning from repeated multiplication. Exploration 1.2 extends this understanding by identifying and generalizing the properties of exponents. Exercise 1.1 institutionalizes exponent knowledge by transforming exponent properties into tools for justification, equation solving, and symbolic simplification. The reconstructed global organization demonstrates a progression from meaning construction to formal mathematical practice. The analysis further shows that the visibility of the praxis block increases throughout the chapter, whereas technological explanations become less explicit during the institutionalization phase. These findings contribute to textbook research by illustrating how the sequencing of praxeological components shapes students' opportunities to construct, generalize, and apply mathematical knowledge. The study also highlights the value of ATD as a framework for examining the epistemological organization of mathematical content in school textbooks